A Study On The Employee Engagement And Grievances In Automobile Industry (Journal of Namibian Studies : History Politics Culture, 2023)
This study is conducted on employees working in automobile industry in chennai to understand the extent of employee engagement in the organization. Employee engagement is the level of commitment and involvement an employee has towards the organization and its values. An engaged employee is known of business context, and works with coworkers to improve performance at the job for the benefit of the organization. It is a positive behaviour held by the employees towards the organization and its values. Engagement at work as the ‘harnessing of organizational members’ selves to their work. A sample size of fifty was taken in order to conduct research. Random sampling technique was used in order to conduct the survey. The data was collected by interviewing the respondents with the help of a structured questionnaire. As a result of implementing these practices, the automobile industries can easily improve organization effectiveness.